Potential Conditions for Linking Teachers' Online Informal Learning with Innovative Teaching. (September 2022) - Tan, Xiujuan; Chen, Peishan; Yu, Haiqin
Highlights: Teachers' online informal learning has a positive effect on innovative teaching. Their relationship is stronger when time pressure is lower. Their relationship is stronger for veteran teachers. Their relationship is stronger for teachers involved in online teacher communities. Abstract: With the advent of the digital era, online informal learning is becoming more common and allows people to choose what, when, and where to study independently and flexibly. However, this new way of learning is also subject to interference from social networking sites, online games, and irrelevant information. Therefore, the effects of online informal learning remain highly uncertain. Although some studies have found that online informal learning is correlated positively with innovation, this result may be limited to the special context of the epidemic. Using a sample of 351 college teachers, this study explores the relationship between teachers' online informal learning and innovative teaching and its influencing factors. The findings demonstrate a significant positive correlation between teachers' online informal learning and innovative teaching, meanwhile, time pressure, teaching experience, and online community moderate the relationship. Specifically, when time pressure was low, online informal learning played a stronger positive role, but as time pressure increased, the positive role of online informal learning decreased. The relationship between online informal learning and innovative teaching was stronger for veteran teachers and for teachers involved in online communities. These results provide guidance on how to promote teachers' innovative teaching through online informal learning in this era of digitization.